CREATIVE ECONOMY: INTERTWINING KNOWLEDGE, ART AND FASHION - Soares, Emilli Karina Cominato; Ghizzo, Marcio Roberto; Dias, Marcelo Capre; Nagamatsu, Rosimeire Naomi (Seven Editora, 2025)
The text explores the relationship between Creative Economy, art and fashion as potential catalysts for economic, social and cultural development. The Creative Economy, which emerged in Australia and spread in Brazil, values "know-how", uniting creativity, culture and sustainability. In Brazil, this economy represents 2.84% of GDP, with annual growth of 6.13%, and has great potential to expand creative exports. Handicrafts and fashion design, core subsectors of the Creative Economy, stand out for adding cultural and social values to products, promoting inclusion and sustainability. Authorial fashion and handicrafts rescue traditional techniques, integrating cultural identity and technological innovation. The Creative Economy faces the challenges imposed by globalization, offering market alternatives that prioritize intangible values, such as creativity and cultural heritage. It is concluded that the strengthening of the interaction between art and fashion, with the support of the government, can generate employment and income, consolidating the Creative Economy as a model of resistance and inclusion in a market dominated by consumerism.DOI: https://doi.org/10.56238/sevened2024.037-137